2020
DOI: 10.1109/jlt.2019.2952466
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Optic Tuning of a Monolithically Integrated Widely Tuneable InP Laser With Free-Running and Stabilized Operation

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…More information on the design and operation of such device structure can be found in Ref. [3]. For testing, the tunable ring laser sample was mounted on a custom thin film AlN ceramic subcarrier and packaged in a 14-pin butterfly package with a PM fiber aligned to the output facet for the collection and analysis of the optical output.…”
Section: Device Design and Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…More information on the design and operation of such device structure can be found in Ref. [3]. For testing, the tunable ring laser sample was mounted on a custom thin film AlN ceramic subcarrier and packaged in a 14-pin butterfly package with a PM fiber aligned to the output facet for the collection and analysis of the optical output.…”
Section: Device Design and Packagingmentioning
confidence: 99%
“…In this paper the authors report the packaging, characterisation and reliability testing of a ring laser 3 that achieves wide tunability with narrow linewidth while maintaining nanosecond switching speeds. This set of characteristics makes the device well suited to applications such as FMCW LiDAR 4 and coherent optical packet switching (OPS) or optical burst switching (OBS).…”
Section: Introductionmentioning
confidence: 99%
“…This technology is commonly employed in a variety of optical and photonics applications, such as modulators, tunable filters, and laser systems. [112][113][114][115] The key principle behind EO tuning is the in-teraction between the electric field and the material's refractive index. When an electric field is applied to a suitable EO material, it induces changes in the material's refractive index, altering the way it interacts with light.…”
Section: Electro-optic Tuningmentioning
confidence: 99%
“…In 2019, Stefanos Andreou et al [47] reported a monolithic integrated InP-based tunable ring-shaped external cavity diode laser. The laser achieved wavelength tuning through a reverse bias voltage-controlled electro-optically tunable ring resonator, which could be continuously tuned to 34 nm.…”
Section: Advances In 155 µM Waveband Monolithic Integrated External C...mentioning
confidence: 99%